Penanganan luka terbuka pada axilla kucing domestik metode skin flapping rotation flaps - Liza Sadda Cakrawati; Ajeng Aeka Nurmaningdyah; Galuh Purnawati; Hasan Ashari; Kirana Sita Pinasthika (VITEK : Bidang Kedokteran Hewan, 2021)
The Domestic Short Hair (DSH) cat is male, age unknown, and body weight 4.25 kg has an open wound on the axilla of the cranial dexter limb. The wound was 5 cm in diameter. The surgery performed was the skin flapping rotation flaps method. Post operative care includes wound cleaning, ceftriaxone antibiotics, and anti-inflammatory ketoprofen. The method of handling in this case can be concluded that skin flapping can be used in the treatment of open wounds in cats.